Determinants of Dividend Policy: An Empirical Analysis of UK Market - Wang, Yue (2006)
To date, a number of studies published on the determinants of dividend policy but studies on particular determinants are lagged behind. It is well known that efficient financial markets in all respects are well performed than the emerging markets. The major objective of this dissertation is to identify the determinants of dividend policy in UK market. All for the period of 1988-1997 are considered as the sample of this study. Ordinary Fixed-effect model models are employed to identify the determinants of dividend policy in the target market. The results indicate that ROA, turnover, firm size and long term liability in the whole debt are positively related to dividend payout; while current liability as while as the whole debt are negatively related to dividend payout. However, growth rate does not show significance with dividend payout as previous literature. All of these coefficients are in the predicted direction and quite consistent with previous empirical evidence except growth rate. These results support transaction cost on dividend policy, but do not deny clientele effect of dividend, the influence of both agency cost and residual theory of dividend. Finally, the results suggest that ROA, turnover, leverage and firm size are the major determinants of dividend policy in UK market. This study may help in understanding the inherent characteristics and the determinants of dividend policy.